2019
DOI: 10.14744/anatoljcardiol.2019.43247
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of serum salusin beta levels with coronary slow flow

Abstract: Relationship of serum salusin beta levels with coronary slow flow Objective: The pathophysiology of coronary slow flow (CSF) has not been clarified. Salusin-β is released predominantly from the atheroma plaques and influences the pathophysiologic processes of atherosclerosis. Therefore, this study aimed to determine serum salusin-β levels in CSF and its correlation with CSF. Methods: The study included 39 patients with CSF, and the control group (n=42) consisted of consecutive subjects with normal coronary art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Several possible mechanisms have been proposed, such as the endothelial dysfunction theory 28 , early atherosclerosis 29 , microvascular disease 5 , 30 , platelet dysfunction 31 , changes in hemorheology 32 , 33 , and oxidative stress and local/systemic inflammatory response 3 5 . Recently, some studies have indicated that lipoprotein-associated phospholipase A2 34 , plasma choline 35 , or serum salusin beta level 36 could be a predictive or diagnostic biomarker for CSF.…”
Section: Discussionmentioning
confidence: 99%
“…Several possible mechanisms have been proposed, such as the endothelial dysfunction theory 28 , early atherosclerosis 29 , microvascular disease 5 , 30 , platelet dysfunction 31 , changes in hemorheology 32 , 33 , and oxidative stress and local/systemic inflammatory response 3 5 . Recently, some studies have indicated that lipoprotein-associated phospholipase A2 34 , plasma choline 35 , or serum salusin beta level 36 could be a predictive or diagnostic biomarker for CSF.…”
Section: Discussionmentioning
confidence: 99%
“…We read the study entitled "Relationship of serum salusin beta levels with coronary slow flow" by Akyüz et al (1) with great interest. In their study, they reported that salusin-β concentrations were associated with the coronary slow-flow phenomenon.…”
Section: Letters To the Editormentioning
confidence: 99%
“…If not, the reliability of the results is doubtful. Therefore, we wish to make the following contributions to this study conducted by Akyüz et al (1).…”
Section: Letters To the Editormentioning
confidence: 99%
See 2 more Smart Citations